2018
DOI: 10.1016/j.molcel.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenine DNA Modification in the Human Genome

Abstract: DNA N-methyladenine (6mA) modification is the most prevalent DNA modification in prokaryotes, but whether it exists in human cells and whether it plays a role in human diseases remain enigmatic. Here, we showed that 6mA is extensively present in the human genome, and we cataloged 881,240 6mA sites accounting for ∼0.051% of the total adenines. [G/C]AGG[C/T] was the most significantly associated motif with 6mA modification. 6mA sites were enriched in the coding regions and mark actively transcribed genes in huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
366
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 434 publications
(409 citation statements)
references
References 50 publications
(105 reference statements)
26
366
4
Order By: Relevance
“…We and others reported that DNA undergoes rare N 6 -mA modification in low and high eukaryotes (Fu et al, 2015; Greer et al, 2015; Wu et al, 2016; Xiao et al, 2018; Yao et al, 2017; Zhang et al, 2015). However, the biological function of N 6 -mA in human cancers remains unclear.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We and others reported that DNA undergoes rare N 6 -mA modification in low and high eukaryotes (Fu et al, 2015; Greer et al, 2015; Wu et al, 2016; Xiao et al, 2018; Yao et al, 2017; Zhang et al, 2015). However, the biological function of N 6 -mA in human cancers remains unclear.…”
Section: Discussionmentioning
confidence: 91%
“…N 6 -mA levels were elevated in other central nervous system cancers, including diffuse intrinsic pontine glioma (DIPG), meningioma, and medulloblastoma, compared to normal human astrocytes (Figure S1D). Of note, a recent study reported high levels of N 6 -mA in normal human adult tissues (at several hundred PPM), with downregulation in gastric and stomach cancers (Xiao et al, 2018). However, our current study, together with other previous studies (Zhu et al, 2018) did not find high levels of N 6 -mA in normal adult tissues or mammalian cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DOI 10.1002/em one study, substrate turnover by TDG was reportedly enhanced by the NEIL enzymes (Schomacher et al, 2016). 2B; Xiao et al, 2018;Kweon et al, 2019). 5hmC may also be deaminated to 5hmU, which can be recognized by TDG, single-strand selective monofunctional U-DNA glycosylase (SMUG1), MBD4, or the NEIL1 DNA glycosylase and repaired via BER (reviewed in Bayraktar and Kreutz, 2018).…”
Section: The Enigma Of Mtdna Methylationmentioning
confidence: 99%